Minimum wages, earnings, and migration - Ernest Boffy-Ramirez (IZA Journal of Migration, 2013)
Does increasing a state's minimum wage induce migration into the state? Previous literature has shown mobility in response to welfare benefit differentials across states, yet few have examined the minimum wage as a cause of mobility. Focusing on low-skilled immigrants, this paper empirically examines the effect of minimum wages on location decisions within the United States. This paper expands upon minimum wage and immigration literatures by demonstrating that the choice of destination is sensitive to minimum wage changes, and that the effects are highly dependent on the number of years an immigrant has resided in the U.S.
Keywords: J15; J61; 330; Migration; Minimum wages; Immigrants; Expected earnings